The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1093/ajcn/nqy255
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity is associated with food intake, snacking, and eating disorders in a general population

Abstract: Background Impulsivity is a psychological trait linked to health issues such as obesity. However, few studies have explored the relation between impulsivity, dietary intake, and eating disorders (EDs) in a general population. Objective The aim of this cross-sectional study was to assess whether impulsivity was associated with energy intake, food-group consumption, snacking, and risk of EDs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 64 publications
5
39
0
2
Order By: Relevance
“…Many factors influence eating behavior, including psychological ones [5]. So far, the literature has largely focused on negative psychological characteristics associated with eating behavior such as emotional eating [6,7], cognitive restraint [8,9] or impulsivity [10,11]. However, more recently, research has started to focus on positive psychological traits that could have a beneficial impact on dietary behavior and nutritional status such as intuitive eating [12] or self esteem [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Many factors influence eating behavior, including psychological ones [5]. So far, the literature has largely focused on negative psychological characteristics associated with eating behavior such as emotional eating [6,7], cognitive restraint [8,9] or impulsivity [10,11]. However, more recently, research has started to focus on positive psychological traits that could have a beneficial impact on dietary behavior and nutritional status such as intuitive eating [12] or self esteem [13] .…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of risk of developing FEDs shows great variability worldwide [36]. Thus, in the general adult population, a recent study including more than 50 000 subjects from the NutriNet-Santè study in France found a prevalence of 14.1 % [37]; another Greek study including 1,865 young adults subjects reported a prevalence of risk of FEDs of 39.7 % [38]. In college students, the prevalence of risk of FEDs was 23.2 % in France [1], a FED prevalence of 9.4 % was found in an American follow-up survey [39], and 38.3 % of female Palestinian college students answered with two or more positive answers in the SCOFF questionnaire [40].…”
Section: Prevalence Of Risk Of Fedsmentioning
confidence: 99%
“…In addition, the broader concept of 'trait' self-report impulsivity is also highly relevant in this context. For example, a recent, large cross-sectional population-based study reported that trait impulsivity on the Barratt impulsivity scale (BIS) was associated with disordered eating (Bénard et al, 2019). In a systematic review, there was evidence from a range of studies that eating disorders were associated with significantly elevated impulsivity on self-report questionnaires (such as BIS) compared to controls (Waxman, 2009).…”
Section: Introductionmentioning
confidence: 99%